1995
DOI: 10.1007/bf00311430
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma levels of soluble thrombomodulin in patients with sepsis and organ failure

Abstract: The fact that thrombomodulin (TM) is released into the bloodstream from damaged vascular endothelial cells led us to hypothesize that plasma levels of soluble TM could be an indicator of the development of organ failure. In this study, we examined the changes in plasma levels of TM in 60 septic patients and 13 postsurgical patients, and investigated the circulating levels of interleukin 6 (IL-6) and polymorphonuclear leukocyte elastase (PMN-E) to determine the mechanism causing the excess liberation of TM. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 22 publications
3
36
0
Order By: Relevance
“…Distinct phosphorylation of ERK by CLEC14A modulation upon stimula-deletion of Clec14a, increased vessel density following severe hemorrhaging appears more reliable. While the greater hemorrhagic potential of tumors in CLEC14A-KO mice is a possible cause of early death, we cannot exclude other potential causes, such as the inflammatory response to hemorrhagic shock or B16BL6 cell infiltration of the lungs (Figure 5Q), particularly since both VEGFR-3 and the CLEC14A paralog thrombomodulin regulate sepsis (52)(53)(54). Further immunological analysis of CLEC14A-deficient mice is required to determine the precise cause of early death.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct phosphorylation of ERK by CLEC14A modulation upon stimula-deletion of Clec14a, increased vessel density following severe hemorrhaging appears more reliable. While the greater hemorrhagic potential of tumors in CLEC14A-KO mice is a possible cause of early death, we cannot exclude other potential causes, such as the inflammatory response to hemorrhagic shock or B16BL6 cell infiltration of the lungs (Figure 5Q), particularly since both VEGFR-3 and the CLEC14A paralog thrombomodulin regulate sepsis (52)(53)(54). Further immunological analysis of CLEC14A-deficient mice is required to determine the precise cause of early death.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble TM is increased significantly in the plasma of septic patients (16); however, its functions in sepsis remain unclear. Our earlier work demonstrated that rTMD1 inhibits LPS-induced inflammation by binding to the Lewis Y Ag on LPS (18), but the function of rTMD23 in LPS-induced inflammation is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…TM consists of a C-type lectinlike domain (domain 1), a domain with six epidermal growth factor (EGF)-like structures (domain 2), a serine/threonine-rich domain (domain 3 [D3]), a transmembrane domain (domain 4), and a cytoplasmic domain (domain 5) (15). Soluble forms of TM are also reportedly high in the plasma of septic patients (16). Because TM is a natural anticoagulant protein, recombinant human soluble TM protein (ART-123) effectively reduces disseminated intravascular coagulation (17).…”
mentioning
confidence: 99%
“…Soluble TM is released from the surface of endothelial cells secondary to increased proteolytic cleavage when endothelial damage occurs [7]. Increased sTM level has been associated with mortality in patients with trauma, acute respiratory distress syndrome, major surgery and sepsis, expressing a correlation with multiple organ failure [5][6][7]. Moreover, increased sTM in patients with atherosclerosis is a predictor of poor cardiovascular outcome and increased levels of sTM, C-reactive protein (CRP) and another inflammatory markers have been reported after percutaneous coronary interventions [15] and have been found to be a predictor of poor outcome in patients surviving acute coronary syndromes [4].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, elevated sTM has been found to predict events in patients surviving an acute coronary syndrome [4], and increased sTM level has been reported in patients with multiple organ dysfunction syndrome (MODS), disseminated intravascular coagulation induced by sepsis or blunt trauma. In all these conditions, sTM has been associated with increased mortality [5][6][7]. Therefore, it has been suggested that the elevation of sTM levels might be associated with a higher inflammatory state [4,8,9].…”
Section: Introductionmentioning
confidence: 99%